लोक की भक्ति : भक्ति की लोक भूमिका - (:unkn) unknown (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2009)
This book emphasizes on the importance of devotion. The contribution of people in devotion is the fundamental of our society and culture .
Lok Ki Bhakti : Bhakti Ki Lok Bhumika
Keywords: लोक की भक्ति : भक्ति की लोक भूमिका; Lok Ki Bhakti : Bhakti Ki Lok Bhumika; Literature; Hindi; Hindi